MEDIATING EFFECT OF BEHAVIORAL INTENTION ON THE INFLUENCE OF PERCEIVED VALUE, ATTITUDE, AND SUBJECTIVE NORM ON VISIT DECISION - Rizky, Fahmi Muhamad; Kurniawan, Khamelya Shafira; Hilmi, Muhammad Rifqi Rahamandika (Jurnal Pariwisata Indonesia, 2024)
Theory of planned behavior is believed to be a theory that can influence visit decisions. Similarly, the dimension of perceived value becomes a determining factor in tourists' decisions to visit. Aims to study analyze the effect of the Theory of Planned Behavior and perceived value on tourists' visit decisions to Alamendah Tourism Village. Data collection using a purposive sample technique, 100 respondents who had visited Alamendah Tourism Village were given questionnaires to complete in order to collect data.. The research method in this study is a quantitative approach, employing descriptive and verificative data analysis techniques with PLS SEM techniques. The data analysis was conducted using SmartPLS version 4.0. The results of this study are: 1) perceived value, attitude, and perceived behavioral control affect behavioral intention; 2) subjective norm does not affect behavioral intention; and 3) behavioral intention influences actual behavior.